Impact of cell culture transition on adipose-derived mesenchymal stromal cells: Multi-omics analysis of small- vs large-scale production - Marina Ramírez Galera; Athanasios Oikonomou; Jonas D. Elsborg; Lisa Harth; Anne Fischer-Nielsen; Marianne Bengtson Løvendorf; Beatrice Dyring-Andersen; Francesco Iorio; Lea Munthe Fog; Anders Woetmann; Jesper Dyrendom Svalgaard (Molecular Therapy: Methods & Clinical Development)
Mesenchymal stromal cells (MSCs) are being tested in numerous clinical trials, yet the limited progression of these trials to advanced stages indicates unresolved translational challenges. Expanding MSCs is a critical step in most therapeutic applications, and bioreactor-based culture offers large-scale production compared to monolayer cultures. Nevertheless, since MSCs sense their microenvironment, it is crucial to understand how these systems affect their properties. We expanded human adipose-derived mesenchymal stromal cells (AD-MSCs) from the same donors in both small- and large-scale platforms. Bulk-RNA sequencing (RNA-seq) and mass spectrometry analysis demonstrated that small-scale culture had a broader range of differentially expressed genes (DEGs) and proteins within immunomodulatory, cell migration, and cell adhesion pathways. In contrast, the large-scale culture showed a lower amount of DEGs and proteins associated mainly with extracellular matrix synthesis. Our findings demonstrate that expansion platforms significantly impact MSCs’ properties, highlighting the need to optimize expansion conditions to obtain high cell yield without compromising MSCs’ attributes.